Implementasi Media Sosial sebagai Sarana Digital marketing pada Divisi Business Services Telkom Bogor - Wafda Syifa Al Mashri; Tasya Camila Hamdani (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
The development of digital technology encourages companies to utilize social media as a digital marketing tool in supporting communication and business service marketing activities. This study aims to analyze the implementation of social media as a digital marketing tool in the Business Services Division of Telkom Bogor and to identify the forms of interaction and audience engagement through social media. This study used a qualitative approach with a descriptive method. Data collection techniques were conducted through observation, semi-structured interviews, and literature studies. The research informants consisted of internal parties involved in managing the company’s social media and followers of the company’s social media accounts as audience representatives. The data were analyzed using thematic analysis techniques. The results showed that social media is utilized as a promotional tool, a medium for delivering service information, increasing Brand awareness, and strengthening relationships with customers. The social media platforms used include Instagram, TikTok, YouTube, Facebook, LinkedIn, and WhatsApp Business, each having different communication functions according to audience characteristics. The implementation of social media is carried out through the stages of content planning, content creation, content publishing, audience engagement, and evaluation and reporting. The findings also indicate that visual content quality, information relevance, and publication consistency influence audience engagement with the company’s social media. Overall, social media is considered effective in supporting the company’s digital marketing activities through interactive digital communication based on audience needs.